Effects of ethanol and three-phase contact angle on gold nanoparticle adsorption at water/toluene interface - Zhao, Qin (2014)
This work investigates the effects of ethanol and the 3-phase (charged Au surface, water/ethanol solution and toluene phase) contact angle on the formation of gold nanoparticle monolayer at water/toluene interface. Although thermodynamic calculation indicates that nanoparticles can be spontaneously adsorbed to the water/oil or water/air interface even without ethanol addition, a large sorption barrier was proposed to hinder the nanoparticle adsorption for the water/air interface. By replacing the air phase with an oil phase (toluene), the sorption barrier was proposed to be reduced to a large extent due to the enhancement in attractive hydrophobic interaction. Besides, ethanol addition was proposed to enhance the nanoparticle adsorption by reducing the repulsive electrostatic interaction. Meanwhile, it was found that the 3-phase contact angle can be adjusted to approach 90 by modulating the ethanol dosage. The effect of ethanol dosage has also been investigated based on the morphology of the monolayer film.